(untitled) (Agrikan Jurnal Agribisnis Perikanan, 2021)
This study aims to determine: (1) the costs, revenues, and profits of the cassava chips home industry in one production process, and (2) the profitability of the cassava chips home industry in one production process. This research was determined by purposive sampling, namely the determination of the sample with a specific purpose. Purposive sampling can be interpreted as sampling based on intentional, Determination of the research area is determined proportionally in the District of Kampak, Trenggalek Regency. The sampling method used in this study is the census method. Where all samples in the research area were taken as samples. The results of the study on cassava chips entrepreneurs in Kampak sub-district, Trenggalek district showed that the average of cassava raw materials was 250 kilograms at the price of cassava at the time of the study of Rp. of 25,000 per kilogram. With the calculation results after the analysis is as follows: (1) the average entrepreneur spends Rp. 1,036,684, generating revenue of Rp. 1,500,000, and an income of Rp. 463,316. (2) The average daily profit generated is 44.69% higher than the bank interest rate of 17.50 per year or 0.05 per day for micro businesses.